Health policy and systems responses to forced migration - Bozorgmehr, Kayvan; Roberts, Bayard; Razum, Oliver; Biddle, Louise (Springer eBook Collection, 2020)
Chapter 1: Health Policy and Systems Responses to Forced Migration: An Introduction -- Chapter 2: The Political Economy of Health and Forced Migration in Europe -- Chapter 3: Innovative Humanitarian Health Financing for Refugees -- Chapter 4: Health Care Financing Arrangements and Service Provision for Syrian Refugees in Lebanon -- Chapter 5: Health Financing for Asylum Seekers in Europe: Three Scenarios towards Responsive Financing Systems -- Chapter 6: Understanding the Resilience of Health Systems -- Chapter 7: Health Security in the Context of Forced Migration -- Chapter 8: Security Over Health: The Effect of Security Policies on Migrant Mental Health in the United Kingdom -- Chapter 9: Evidence on Health Records for Migrants and Refugees: Findings from a Systematic Review -- Chapter 10: Assessing the Health of Persons Experiencing Forced Migration: Current Practices for Health Service Organisations -- Chapter 11: Discrimination as a Health Systems Response to Forced Migration -- Chapter 12: Health Systems Responsiveness to the Mental Health Needs of Forcibly Displaced Persons -- Chapter 13: Global Social Governance and Health Protection for Forced Migrants.